Enzymatic Inactivation of a New Aminoglycoside Antibiotic, Sisomicin, by Resistant Strains of Pseudomonas aeruginosa - O'Hara, K. (1974)
The antibacterial activity of sisomicin (SS), a new aminoglycoside antibiotic active toward clinical isolates of Pseudomonas aeruginosa, was determined and compared with that of the gentamicin C complex. Both drugs were effective against these strains and showed almost the same antibacterial activity. A few strains were found to be resistant to SS. The antibiotic was inactivated by a cell-free extract from the SS-resistant strains due to acetylation of the drug. Comparative studies of the inactivation of the drugs which lack a 6′-amino group in the amino sugar linked to 2-deoxystreptamine strongly suggested that SS inactivation was due to acetylation of the 6′-amino group of the 4′,5′-didehydropurpurosamine moiety.